“Yerevan State Conservatory after Komitas in the light of geopolitical changes” - Movsisyan, Цовинар Грайровна (Musical Armenia, 2024)
On April 25-26, 2023, the Gnesin Russian Music Academy hosted a conference titled “Cooperation of CIS Countries in the Field of Music and Creative Education”. It was chaired by GRMA rector Alexander Ryzhinsky, and was dedicated to the problems of education in the fields of contemporary music, the arts, and theater. The problems of education in the arts remains high on the agenda of UNESCO projects, due to their importance and significance. It is a well-known fact that music and arts educational institutions have to lead an unequal “straggle” for being in cluded in the Top Ten List of the world's best universities, competing with the IT sector. This conference was the result of many years of work. This all started in 2011, when the Concept on Education in Culture and Arts of the CIS Member States was signed in Minsk. In 2014, the Gnesin Russian Academy of Music became the base organization for music and education. In 2023, sixteen participants from eight countries were invited to the conference in Moscow. Armenia was represented by the Yerevan State Conservatory after Komitas, represented by vice-rector Tsovinar Movsisyan, and the State Academy of Arts, represented by Nune Minasyan, head of the Center of Education Quality Assurance. The participants were assigned to demonstrate the existing challenges rather than showcase their achievements. In her speech, Tsovinar Movsisyan, PhD in Art History, addressed the problem of academic competition at different levels. She suggested exchanging ideas on the introduction of doctoral studies and sharing participants' experiences regarding the differentiation of academic titles and degrees (e.g., How How will those with the scientific title of "Doctor of Arts" differ if all "PhD"s are going to be called "doctors"? ). An agreement was reached to expand the existing cooperation as well as to carry out academic student exchanges. However, taking into account that teachers motivation seems to be a greater challenge, it was decided to initiate teacher training and professional development programs, to organize joint competitions and festivals, and to create new forms of mutual cooperation using distance technologies. Rector A. Ryzhinsky proposed to organize new specialized courses, in particular on piano tuning and sound design. Tsovinar Movsisyan specified that these qualifications had only recently been included in the curriculum of the Gnesin Academy. The results of this innovation will be understood within a year, with the first graduates of the program. The participants confirmed their willingness to provide the necessary accommodations; along with that, it was planned to use the online education system for theoretical courses while holding practical classes in person on a full schedule. The YSC vice-rector for science emphasized the keen interest in Armenia shown by the conference participants, as well as the general atmosphere of engagement and common interests. Two weeks before the conference, Drs Alexander Ryzhinsky and Dina Kirnarskaya at the highest level were representing the Gnesin Academy at the events marking the anniversary of S.V. Rachmaninov at Yerevan State Conservatory after Komitas. In their speech at the two-day summit, they mentioned the everyday dedicated work of our teaching staff despite the consequences of the war. The conference highlighted the commonality of the aspirations in the cultural space of the CIS countries, the importance of professional cooperation, and the commitment of the participants to support these processes. Dina Kirnarskaya, the vice-rector of the Gnesin Academy and UNESCO representative, is convinced that "we will grow closer, understand each other, and cooperate better. Culture, arts, and education will prevent people from losing the communication bridges.